LED lighting and exogenous cytokinin enhance budbreak and winter growth of ‘Washington’ navel orange in the nursery - de Carvalho, Deived Uilian; Bisi, Rayane Barcelos; Bowman, Kim D.; Albrecht, Ute (Frontiers in Plant Science, 2025)
Citrus nurseries typically reduce budding activity during winter due to weak growth from short photoperiods and low temperatures. Modern light-emitting diodes (LEDs) and exogenous application of plant growth regulators (PGRs), such as the synthetic cytokinin 6-benzylaminopurine (BA), may mitigate these winter challenges by extending daylength and stimulating budbreak. We report in this paper the effects of different LED spectra and BA on budbreak and growth of ‘Washington’ navel orange (Citrus × sinensis) grafted on two rootstocks during winter. A 4 × 2 × 2 factorial design was used, including four light levels (NoSL, no supplemental light; FSL, full supplemental light from budding to 12 weeks after budding (wab); BWSL, blue and white supplemental light from budding to 12 wab; and BWSL-FSL, BWSL from budding to 6 wab changing to FSL from 6 to 12 wab), two rootstocks (Carrizo citrange, C. × sinensis × Poncirus trifoliata; and Rubidoux trifoliate orange, P. trifoliata), and two PGR levels (NoBA and BA). Each treatment was replicated six times with 24 plants per replicate, totaling 2304 experimental plants. Different horticultural responses were assessed over time. Both FSL and BWSL-FSL significantly improved budbreak (79% and 77%, respectively) and survival (80% and 77%, respectively) compared to NoSL (62% and 64%, respectively). Budbreak was 1.3-fold higher on Carrizo than on Rubidoux. When supplemented with FSL, Carrizo produced the largest rootstock diameter (7.80 mm), scion diameter (4.37 mm), total leaf area (678 cm²), and scion dry biomass (7.87 g), representing a 5.7-fold increase compared to Rubidoux without supplemental light (1.38 g). Carrizo plants supplemented with FSL had more nodes (16) and longer internodes (34.5 mm) compared to NoSL (10 nodes and 17.5 mm, respectively) and BWSL (13 nodes and 25.4 mm, respectively). BA application improved horticultural responses regardless of rootstock, and the combination of BWSL and BA enhanced chlorophyll content compared to most of the other treatment combinations. These findings confirm the effectiveness of tailored LED light, suitable rootstock selection, and PGR strategies in optimizing citrus nursery production and tree quality during the winter months when natural light is limited.